Genetic parameters and character association of yield and its attributes in Indian mustard (Brassica juncea L.) - Sangeeta Kumari; K Srivastava; Ayushi Srivastava; Akanksha (Journal of Oilseed Brassica, 2026)
Thirty eight genotypes of Indian mustard along with check Giriraj were evaluated in Randomized block design with threereplications during Rabi 2016-17. The ANOVA suggested the existence of sufficient variability between genotypes andmean indicated that seed yield per plot showed highest performance followed by number of siliqua per plant and plantheight. High heritability coupled with high genetic advance was found for days to 50% flowering, number of siliqua/plant, siliqua length, seeds/ siliqua, 1000-seed weight, seed yield/ plant, seed yield/plot, biological yield and seed yield(q/ha) suggesting presence of additive gene action for these traits hence direct selection for these traits may prove to berewarding. Higher genotypic coefficient of variation coupled with higher phenotypic coefficient of variation was recordedfor seeds/ siliqua. At genotypic level seed yield was positively correlated with plant height, number of secondarybranches, number of siliqua/ plant, siliqua length, main raceme length, number of siliqua on main raceme, test weight,seed yield/plant, seed yield/ plot and biological yield therefore these traits can be considered for direct selection Atphenotypic level, path coefficient analysis revealed positive direct effect on seed yield (q/ha) for plant height, numberof primary branches/ plant, number of secondary branches/ plant, siliqua length, seeds/ siliqua, main raceme length,number of siliqua on main raceme and number of siliqua/ plant. Since seed yield per plot and biological yield showed highheritability, high genetic advance and positive correlation with the seed yield (q/ha) which was supported by the pathanalysis, therefore, we can use these two traits as selection criteria in breeding programmes. RVM-2 (17.3 q/ha), RGN-73(16.4 q/ha), JD-6 (16.2 q/ha), RGN-298 (15.9 q/ha) and RGN-48 (15.8 q/ha) were found better than Giriraj for seed yield.